2021
DOI: 10.1093/ptep/ptab055
|View full text |Cite
|
Sign up to set email alerts
|

Systematic study on the role of various higher-order processes in the breakup of weakly-bound projectiles

Abstract: The virtual photon theory (VPT), which is based on first-order Coulomb dissociation restricted to the electric dipole (E1), has been successfully used to explain the breakup data for several cases. Our aim is to study the role of various higher-order processes that are ignored in the VPT, such as the nuclear breakup, interference between nuclear and Coulomb amplitudes, and multistep breakup processes mainly due to strong continuum-continuum couplings in the breakup of two-body projectiles on a heavy target at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Various studies have shown the significant role played by dynamical effects in both Coulomb-and nuclear-dominated breakup reactions and how they can affect the analysis of the data for both nuclear-structure and astrophysical applications [12][13][14][15][16][17][18]. The dynamics of the diffractive breakup is well treated by state-of-the-art models such as the continuumdiscretized coupled channel method (CDCC) [12,19,20], time-dependent approach [21][22][23][24], and eikonal-based models such as the eikonal-CDCC (E-CDCC) [25,26] and the dynamical eikonal approximation (DEA) [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown the significant role played by dynamical effects in both Coulomb-and nuclear-dominated breakup reactions and how they can affect the analysis of the data for both nuclear-structure and astrophysical applications [12][13][14][15][16][17][18]. The dynamics of the diffractive breakup is well treated by state-of-the-art models such as the continuumdiscretized coupled channel method (CDCC) [12,19,20], time-dependent approach [21][22][23][24], and eikonal-based models such as the eikonal-CDCC (E-CDCC) [25,26] and the dynamical eikonal approximation (DEA) [27,28].…”
Section: Introductionmentioning
confidence: 99%